XPS Spectra Analysis of Ti2+, Ti3+ Ions and Dye Photodegradation Evaluation of Titania-Silica Mixed Oxide Nanoparticles - Chinh, Vu Duc; Broggi, Alessandra; Di Palma, Luca; Scarsella, Marco; Speranza, Giorgio; Vilardi, Giorgio; Thang, Pham Nam (Journal of electronic materials, 2018)
TiO 2 -SiO 2 mixed oxides have been prepared by the sol–gel technique from tetrabutyl orthotitanate and tetraethyl orthosilicate. The prepared materials were characterized by x-ray diffraction, scanning electron microscopy, energy dispersive x-ray spectroscopy, nitrogen physisorption, Fourier-transform infrared spectroscopy (FT-IR) and x-ray photoelectron spectroscopy (XPS). The results indicate that the TiO 2 -SiO 2 mixed oxides have a large surface area and a nanoscale size. FT-IR spectra show that Ti atoms are bonded to silica by oxygen bridging atoms in Ti-O-Si bonds. The titanium valence states in TiO 2 -SiO 2 mixed oxides were investigated by XPS, and their spectra report the presence of Ti 2+ and Ti 3+ cations for high silica concentration, suggesting the formation of oxygen vacancies. The photocatalytic activity of the prepared materials has been evaluated for the photodegradation of methylene blue (MB). The mixed oxides were activated by means of a UV light source, and the concentration of MB was monitored by UV–Vis spectroscopy. The synthesized TiO 2 -SiO 2 shows significantly higher MB removal efficiency in comparison with that of the commercial TiO 2 Degussa, P25. Graphical Abstract In this paper, we observed three valence states of titanium: Ti 4+ , Ti 3+ and Ti 2+ in TiO 2 -SiO 2 40%. This issue has not yet been reported. XPS analysis show that the content of Ti 2+ and Ti 3+ amounts to 25.26 at.% and 13.08 at.%, respectively, while the concentration of Ti 4+ is 61.72 at.%, much lower than in the TiO 2 -SiO 2 9% sample. This behavior is explained observing that in TiO 2 -SiO 2 40%, Ti 4+ is reduced to Ti 3+ and Ti 2+ to a larger extent with respect to TiO 2 -SiO 2 9%.